A Study On The Facilities-Related Issues In High-Rise Residential Building - Paurnami, Sellathurai (2021)
Living in a high-rise residence is now becoming a trend of lifestyle among Malaysian. High-rise residential buildings are a kind of housing with multi-dwelling units constructed on the same site. The rising costs of land have made this form of housing common each year in an urban area. The residents must create a Management Corporation in contrast to their lands on a residential high-rise to control and maintain all of the facilities the developer provides for as stipulated by the Strata Title Act of 1985. In all urban landscape of Malaysia, many residential high-level projects have mushroomed. However, the theory of architectural design, particularly the concept of passive design, is restricted for high-rise buildings. The role represented by management in managing the residential property is crucial to ensuring that all problems solved have an excellent result. Sadly, there have been many problems with the management of high-rise residences, in particular with building maintenance, defects/fault and design/fault design. The semi-structured interview will be conducted with five executive or managers to discuss the issues from a management perspective. And data collection by questionnaire surveys among residents, developers, contractors, architect and other stakeholders. The result found that management has had a range of issues and concerns, such as design, construction defects and insufficient/poorly maintained facilities. To minimise problems and to create excellent conditions of highrise housing, cooperation between developer, management and the resident is obligatory. The focus of this research is on sustainable facility management, we have used resident satisfaction levels to identify and measure factors that lead to dissatisfaction between buyers and consequences related to the issues.